Perancangan dan Implementasi User Interface dan User Experience Aplikasi Monitoring Perkembangan Studi Mahasiswa - Sabila, Alifia (The Indonesian Journal of Computer Science, 2024)
The Bachelor of Information Systems program at Telkom University faces challenges in monitoring four key performance indicators: on-time graduation rates, student withdrawals, students exceeding the normal study period, and critical students. These indicators are crucial for evaluating academic effectiveness and maintaining accreditation. Currently, monitoring is performed semi-manually, which is ineffective and error-prone. This study aims to design and implement a monitoring application using the Design Thinking method, involving empathize, define, ideate, prototype, and testing stages. The application was tested using Maze tools and the System Usability Scale (SUS). Results showed MAUS scores of 91 for students, 88 for guardian lecturers, and 88 for heads of study programs. SUS average scores were 85.8 for students, 84 for guardian lecturers, and 65 for heads of study programs. The application was well-received by students and lecturers but needs improvement for heads of study programs.